Imaging the interaction: Epileptic discharges, working memory, and behavior. Issue 11 (19th June 2012) - Chaudhary, Umair J.; Centeno, Maria; Carmichael, David W.; Vollmar, Christian; Rodionov, Roman; Bonelli, Silvia; Stretton, Jason; Pressler, Ronit; Eriksson, Sofia H.; Sisodiya, Sanjay; Friston, Karl; Duncan, John S.; et al.
<x xml:space="preserve">Abstract</x> Interictal generalized epileptiform discharges may impair cognition. We used simultaneous video‐electroencephalography and functional imaging to quantify changes, induced by epileptiform discharges, in the task‐related activations during a spatial working‐memory paradigm. The number of epileptiform discharges increased during the task with its level of complexity, but were not significantly associated with wrong responses during the task. We observed hemodynamic responses in working‐memory related frontal‐lobe‐network, motor‐cortex, precuneus, and parietal lobes in the absence of epileptiform discharges. In the presence of epileptiform discharges during the task, task‐related hemodynamic changes were seen only in motor‐cortex, precuneus, and parietal lobes. These findings suggest that generalized epileptiform discharges during a high demanding working memory task may change the working memory‐related hemodynamic responses in frontal‐lobe‐network. Hum Brain Mapp 34:2910–2917, 2013. © 2012 Wiley Periodicals, Inc.